The Trans-Pacific Strategic Economic Partnership Agreement: A Critical Analysis - GAO, Henry Shuchao (Institutional Knowledge at Singapore Management University, 2010)
When the Trans-Pacific Strategic Economic Partnership Agreement (TPP Agreement or P4 Agreement) was signed in 2005, it was hailed as a ‘high-standard’ agreement that could serve as a model for Free Trade Agreements (FTAs) within the Asia-Pacific region. This claim seems to have received support from recent events, such as the launch of the accession negotiation by the US and the expression of interests from a host of other countries.This article provides a critical analysis on whether the TPP Agreement is a ‘high-standard’ agreement as its members have claimed. After comparing it with other FTAs, this article notes that the P4 Agreement does not distinguish itself among FTAs and has failed to provide higher market access concessions or stricter disciplines on protectionist policies. This is followed by a discussion on the possible factors that might explain the mismatch between the rhetoric and reality of the P4 Agreement. This article concludes by considering how the P4 Agreement could be re-engineered to fulfil its original expectations.